RESOLUSI KONFLIK PEMBELAJARAN JARAK JAUH DALAM PRESPEKTIF TEORI TEKNOLOGI KOMUNIKASI - Puryanto, Sidik (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Distance learning has become a global trend in the field of education, but conflicts have emerged as a significant challenge in this context. This article outlines potential conflicts that may arise in distance learning, such as technical conflicts, physical/intellectual limitations, student-teacher relationships, student-to-student interactions, conflicts with educational institutions, as well as psychological and evaluation-related conflicts. Using the perspective of communication technology theory, this study demonstrates how communication media play a role in influencing conflicts and their resolutions. The theory of medium richness illustrates the richness of media in delivering information and facilitating interactions, which impact conflict resolution. The sociotechnical systems (STS) approach emphasizes the importance of integrating technology, humans, and the environment in addressing conflicts. The theory of media ecology (ME) illustrates how media influence individual perceptions and behaviors. Conflict resolution strategies based on communication technology theory encompass effective communication, technology training, guidelines and procedures, media monitoring, and increased social interaction. Resolving conflicts in distance learning is crucial for enhancing learning effectiveness, student motivation, student-teacher relationships, mental well-being, and the credibility of educational institutions. While technological strategies are important, human and environmental factors also play a role in preventing and resolving conflicts. In conclusion, conflict resolution strategies based on communication technology theory can assist educational institutions in creating a more positive distance learning experience for students and teachers, while considering both technological and human-environment aspects.